Language Acquisition of Declarative and Imperative Sentences in five-year-old Children - Budi, Wahyu; Halimah, Nur; Indarto, Heri (CV. Tripe Konsultan, 2024)
This study aims to describe the language acquisition of a five-year-old child. This research focuses on declarative and imperative sentence forms, using a descriptive qualitative approach with recording techniques. The analysis results show that the syntactic acquisition in declarative sentences has four forms, and imperative has five. The category of language acquisition at the syntactic level is good enough because there is minimal deviation from the form of speech produced. In summary, five-year-old children will likely use declarative and imperative sentences as they develop their language skills. They may start to use declarative sentences more naturally to convey information and use imperative sentences to express commands or requests, although their usage of these sentence types may vary in complexity and grammatical accuracy. Shortly, the results showed that children's utterances dominate in imperative sentences.